IL-4 induces cAMP and cGMP in human monocytic cells - B. Dugas; N. Paul-Eugene; K. Yamaoka; C. Amirand; C. Damais; J. P. Kolb (Mediators of Inflammation)
Human monocytes, preincubated with IFN-γ respond to IL-4 by a cGMP increase through activation of an inducible NO synthase. Here, IL-4 was found to induce an accumulation of cGMP (1 – 3 min) and cAMP (20 – 25 min) in unstimulated monocytes. This was impaired with NOS inhibitors, but also with EGTA and calcium/calmodulin inhibitors. These results suggest that: (1) IL-4 may stimulate different NOS isoforms in resting and IFN-γ activated monocytes, and (2) cAMP accumulation may be partially dependent on the NO pathway. By RT-PCR, a type III constitutive NOS mRNA was detected in U937 monocytic cells. IL-4 also increased the [Ca2+]i in these cells. Different NOS may thus be expressed in monocytic cells depending on their differentiation and the signals they receive.